The Handbook of fixed income securities - Fabozzi, Frank J.; Mann, Steven V.; Gale Group (New York McGraw-Hill, 2005)
Comprehensive survey of current knowledge of global fixed income marketplace. Provides facts and formulas for finance professionals with emphasis on applications, electronics trading, and global portfolio management. Features contributions from leading academics and practitioners.
Background -- Basic analytics -- Securities -- Credit analysis and credit risk modeling -- Valuation and analysis -- Bond portfolio management -- Derivatives and their applications -- Convertible securities.
1497 p. from this publication (viewed 26 July 2013).
Electronic reproduction.
Keywords: Bonds -- Handbooks, manuals, etc; Preferred stocks -- Handbooks, manuals, etc; Money market funds -- Handbooks, manuals, etc; Mutual funds -- Handbooks, manuals, etc; Fixed-income securities -- Handbooks, manuals, etc; Electronic books